Fetal therapy with fetoscopic laser coagulation in monochorionic twin pregnancy complicated by twin-twin transfusion syndrome - Meller, César; Vázquez, Lucía; Cambiaso, Olivia; Aiello, Horacio; Otaño, Lucas (Revista del Hospital Italiano de Buenos Aires, 2013)
About 30% of monochorionic twin pregnancies have severe complications and the distinction between high-risk monochorionic and lower-risk dichorionic twin pregnancies can be accurately achieved in the first-trimester scan. This distinction is fundamental in order to establish the appropriate follow-up and, if necessary, to offer a treatment. Twin-win transfusion syndrome (TTTS), which complicates 8-15% of the monochorionic pregnancies, is the most important cause of death and handicap in this group. TTTS is thought to arise from an intertwin transfusion imbalance across the vascular anastomoses with hypervolemia, polyuria and polyhydramnios (excess of amniotic fluid) in the recipient, and hypovolemia, oliguria and oligo-anhydramnios (deficit of amniotic fluid) in the donor. Fetoscopic laser coagulation of the vascular anastomoses is the only curative and currently the best available treatment to improve perinatal outcome. We present a case report of a monochorionic diamniotic twin pregnancy complicated with TTTS and a review on this issue